China's Contribution to Development Cooperation: Ideas, Opportunities and Finances - Justin Yifu Lin; Yan Wang (Fondation pour les études et recherches sur le développement international (FERDI), 2015)
Conventional economic theories seem to be inadequate in explaining the diverse and multipolar world we live in. Having lost confidence in the Washington consensus, developing countries are increasingly looking East for development experiences and ideas: what worked, why and how. This paper examines China's role in development cooperation from the angle of structural transformation as a major driver of growth and job creation. Being a bit ahead in the structural transformation process, China can contribute ideas, tacit knowledge, implementation capacity, opportunities as well as finances. Based on a joint learning model, developing countries choose partners based on their respective comparative advantages, instruments of interaction and degree of complementarity. Countries that have a higher number of revealed comparative advantage (RCA) in sectors that needed strongly would be in a better position to help in structural transformation. We use empirical evidence to show that China-financed infrastructure projects do address Africa's infrastructure bottlenecks, and in addition, China's industrial upgrading and outward investment provide opportunities for light manufacturing development in low-income developing countries. Further, expanding the definitions of international aid or cooperation could induce more development financing from various sources. Rationales of China-led grand vision of "One Belt One Road" are discussed.
Keywords: F35; 330